ANALISIS KINERJA KARYAWAN MELALUI FAKTOR-FAKTOR BUDAYA ORGANISASI DAN KUALITAS SISTEM INFORMASI AKUNTANSI (STUDI PADA BADAN KEUANGAN DAN ASET DAERAH KABUPATEN BANDUNG) - Ari Bramasto; Neni Astini; Putri Harissa (Department of Accounting, Faculty of Economics and Business, Universitas Tadulako, 2022)
This take a look at examines the elements that have an effect on the overall performance of personnel of the Regional Financial and Asset Agency of Bandung Regency, particularly via Work Culture and Accounting Information Systems. The studies approach used on this studies is descriptive verification, in the meantime the approach of evaluation used is a couple of linear regression the usage of the IBM SPSS 23 software. This take a look at used purposive sampling with a complete of forty six respondents. The outcomes indicated that the paintings subculture and accounting statistics gadget had a high-quality and giant impact on worker overall performance.